Identification of basic technology difficult topics as perceived by upper basic education teachers and students in Ibadan metropolis / Abd-El-Latif Adekunle Abd-El-Aziz, Jelil Adebayo Jimoh and Abdullahi Muhammad Hassan - Abd-; Jimoh, Jelil Adebayo; Muhammad Hassan, Abdullahi (2020)
The study identified basic technology difficult topics in upper basic curriculum as perceived by teachers and students in Ibadan metropolis. A research question and one hypothesis guided the study. The study adopted a descriptive survey of the correlational research design using multi-stage sampling technique. "Questionnaire for Identification of Basic Technology Difficult Topics in Upper Basic Education" (QIBT-DTUBE) was the main instrument for data collection. Face and content validity of QIBT-DTUBE was established by three technology education experts. The reliability coefficient for QIBT-DTUBE yielded 0.91 using Cronbach Alpha reliability technique. Research questions were analyzed using Mean and Standard deviation while the null hypotheses were tested at .05 level of significance using t-test statistics. Result obtained indicated that teachers and students perceived ten topics as difficult to teach and learn while the students identified additional nine topics that are difficult to learn. More so, a significant difference exists between the mean ratings of upper basic education teachers and students on their perceived levels of difficulty of basic technology topics. Based on these findings, it was recommended among others that basic technology specialist teachers be supported with appropriate trainings and refresher courses on all the topics identified as difficult.